Student Empowerment and Research Unit (SERU): a case study in enhancing development of soft skills among tertiary institutional students - Al-Sadat, N.; Yusof, R.; Yunus, F.; Maznah, R.; Ng, L.L. (2011)
Student Affairs Division in University of Malaya launched a unit called SERU in late 2010 to enhance the development of soft skills among our undergraduates in order to increase employability and value of our graduates. This case study describes the process of empowering the students via student designed programmes in detail. It is envisioned that empowerment is driven by student engagement programmes through a unique "training the trainers" module that results in high impact and yet cost effective sustainable student driven projects which will be evaluated and assessed in phases. Other issues like the challenges faced in the setting up of the unit and the methodology used in empowering the students are also described in the paper. The paper also reports the findings of a needs analysis conducted through key informant and user surveys (a qualitative study). The need analysis is done to highlight the gaps in soft skills needed by the students and aid in mapping the strategies to resolve it. It is hoped that with sharing the case study, this will lead to improvement in student driven projects that can be instituted in other tertiary institutions in other parts of the world.